Efficiency of cloprostenol treatment for uterine infections in cycling cows - Ferreira, Ademir de Moraes; Vetromila, Marcos Antonio Monks; Pires, Maria de Fátima Ávila (Pesquisa Agropecuaria Brasileira, 2014)
Fifty Holstein x Zebu crossbred cows were monitored in several dairy farms. All cows showed mucopurulent discharge from the uterus and a cyclical corpus luteum in one of the ovaries. This condition was observed by rectal palpation and vaginoscopy. Seven days after the natural oestrus, thirty cows were treated with 500 µg intramuscular injection of cloprostenol to induce a new oestrus. A second dose was applied in seven of the 12 cows in which infection persisted seven days after oestrus. In the treated group, 18 cows (60%) recovered with only one injection, while 23 cows (76,7%) did with up to two injections. Among twenty cows of the untreated group (control), only five (25%) recovered from metritis. Number of recovered cases was significantly different between groups (P <0.05). This fact should recommend the use of cloprostenol for treating uterine infections in cycling cows.